Navigating antimicrobial use in Indian freshwater aquaculture: Regulatory frameworks and sustainable alternatives - Gulla Gnaneshwar; Neha W. Qureshi; Abhilash Thapa; Ganesh Kumar; Naila M. Bhat (Journal of Indian Fisheries Association, 2023)
Freshwater aquaculture drives over 95% of India’s production but intensified practices lead to disease and antimicrobial usage, causing antimicrobial resistance. Many developing nations lack regulations, resulting in unchecked antibiotic use and compromised health management. It is noteworthy that while antibiotic usage in brackish water aquaculture is stringently monitored due to international regulations for seafood exports, the same rigor is absent in freshwater aquaculture. A comprehensive study, conducted primarily in Andhra Pradesh, spotlighted the antibiotic landscape in India’s aquaculture industry. Notably, Andhra Pradesh is at the forefront of aquaculture efforts. The study scrutinized antimicrobial regulations in other nations and explored alternative strategies, with the aim of proposing effective measures for regulating antimicrobial usage in Indian freshwater aquaculture. The study collected primary and secondary data through a survey conducted in West Godavari and Krishna districts of Andhra Pradesh and research articles, proceeding papers, government institution websites respectively. The study highlighted that a significant proportion of antibiotics are utilized in Indian freshwater aquaculture farms, with Enrofloxacin, Oxytetracycline, Cephalexin, Doxycycline, and Erythromycin being the most commonly used antibiotics. It proposed alternatives like antimicrobial peptides, herb extracts, pro-, pre-, synbiotics, and vaccination. The study underscored the urgency of further research in this realm and suggests tight antibiotic regulations, required aquaculture prescriptions, and limited drug choices to counter overuse. Other countries’ successful strategies, like strict regulations, vet engagement, records, and alternatives, provide a model to cut antibiotic use. By adopting these steps, India can proactively curb misuse, safeguard aquatic ecosystems, and lower risks of antibiotic-resistant pathogens to the environment and health.